2018
DOI: 10.1111/cyt.12516
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of high‐grade cervical intraepithelial neoplasia in women with persistent high‐risk HPV genotypes and negative cytology

Abstract: This is the first study to report results for women referred to colposcopy with cytology negative, persistently positive hrHPV. Disease prevalence is low, although women with HPV16 have a significantly higher likelihood of high-grade disease compared to other HPV subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…In this study, the HR-HPV infection rate was 6.90% (601/8712), and notably, HPV 52 emerged as the most common genotype, diverging from the findings in other studies [ 17 , 18 , 19 ]. Nevertheless, these results align with previous research [ 20 , 21 ], indicating that HPV 16/18 positivity poses the highest risk for HSIL and lesions of greater severity. This underscores the importance of heightened attention to pregnant women with HPV 16/18 infections compared to those with other HPV genotypes.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the HR-HPV infection rate was 6.90% (601/8712), and notably, HPV 52 emerged as the most common genotype, diverging from the findings in other studies [ 17 , 18 , 19 ]. Nevertheless, these results align with previous research [ 20 , 21 ], indicating that HPV 16/18 positivity poses the highest risk for HSIL and lesions of greater severity. This underscores the importance of heightened attention to pregnant women with HPV 16/18 infections compared to those with other HPV genotypes.…”
Section: Discussionsupporting
confidence: 92%
“…In recent years, it has been established that high-grade cervical neoplasia and invasive cervical cancers are caused by persistent infection with hrHPV [ 6 , 12 ]. Primary HPV screening is significantly more sensitive for high-grade disease prediction than cytology alone [ 13 ]. Long-term data from HPV screening trials indicate a low risk of high-grade CIN in HPV negative and cytologically negative patients [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the quality of colposcopy, only adequate colposcopic settings were performed by two senior consultants. The rate of inadequate colposcopy in patients with persistent hrHPV varies in literature between 0.59% [ 17 ], and 4.8% [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal cytology rate has decreased in Wales following conversion to HPV-based screening in 2018 as hrHPV negative cases do not have cytology triage. Moreover, delayed referral of those with negative cytology potentially prevents overtreatment of regressive SIL as approximately 40% of these women clear HPV in 12 months [23]. In the UK, women would be referred to colposcopy with HPV persistency at 12 or 24 months in the absence of any cytological abnormality.…”
Section: Cytologymentioning
confidence: 99%
“…Macdonald et al [23] reported retrospective data from 1076 women who were hrHPV positive and cytology negative and having further triage with HPV 16/18 typing as part of the Sentinel Sites Pilot. Management depended upon typing with HPV 16/18 seen in colposcopy after first repeat if unchanged at 12 months and with HPVO seen in colposcopy if still unchanged 12 months later.…”
Section: Combined Triage Testsmentioning
confidence: 99%